The Minangkabau Entrepreneurs: The Trait Strategies for Marketing, Financial, and Operational Performance - Wardana, Miko Andi; Tresnasari, Rini; Parwita, Gde Bayu Surya; Nurlia, Nurlia; Yuwanda, Tonny (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
Minangkabau entrepreneurs in Indonesia offer a unique perspective on the trait-based entrepreneurial lineage, as they are culturally reinforced by their distinctive cultural norms, including their psychological aspects. This study aims to investigate the performance of marketing, financial, and operational as observed from their creative self-efficacy, intellectual capital, innovative work behavior, and the mediating role of perceived organizational support. This study adopts a quantitative approach where questionnaires are distributed to 254 MSMEs for path analysis construction using PLS-SEM. This study provides evidence that Minangkabau entrepreneurs exhibit innovative behavior and provide trait-based support to their employees, further enhancing their marketing, financial, and operational performance. The government can accelerate the digital transformation and innovation of MSMEs in Indonesia by exploiting these traits in the construction of their policies.